2004
DOI: 10.1007/s11172-005-0201-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of isomeric 3-phenyl-5-(pyridylmethylene)-2-thiohydantoins and their S-methylated derivatives. Molecular and crystal structures of (5Z)-3-phenyl-5-(pyridin-2-ylmethylene)-2-thiohydantoin and (5Z)-2-methylthio-3-phenyl-5-(pyridin-2-ylmethylene)-3,5-dihydro-4H-imidazol-4-one

Abstract: Three procedures were used for the synthesis of α , β , and γ pyridyl substituted (5Z ) 3 phenyl 5 (pyridylmethylene) 2 thiohydantoins: the reaction of 2 thiohydantoin with the corresponding aldehyde in AcOH in the presence of AcONa, the two step one pot synthe sis with the use of the same starting compounds, and three component condensation of aryl isothiocyanate, glycine, and aldehyde in AcOH. Alkylation of the resulting thiohydantoins with iodomethane in the presence of a base afforded the corresponding S m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 15 publications
(10 reference statements)
0
15
0
Order By: Relevance
“…In the case of α Py substituted ligands 1 and 4, chelate tetrahedral complexes of composition L•MCl 2 were obtained. The structures of cobalt deriva tives 1a 24 and 4a and copper complex 1c were established by X ray diffraction in the present study and in the earlier publication. 24 Apparently, the coordination environment of the cen tral metal ion in the complexes of composition 2L•MCl 2 with β and γ Py substituted ligands 2 and 3 differs from that in the above described complexes.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…In the case of α Py substituted ligands 1 and 4, chelate tetrahedral complexes of composition L•MCl 2 were obtained. The structures of cobalt deriva tives 1a 24 and 4a and copper complex 1c were established by X ray diffraction in the present study and in the earlier publication. 24 Apparently, the coordination environment of the cen tral metal ion in the complexes of composition 2L•MCl 2 with β and γ Py substituted ligands 2 and 3 differs from that in the above described complexes.…”
Section: Resultsmentioning
confidence: 67%
“…The structures of cobalt deriva tives 1a 24 and 4a and copper complex 1c were established by X ray diffraction in the present study and in the earlier publication. 24 Apparently, the coordination environment of the cen tral metal ion in the complexes of composition 2L•MCl 2 with β and γ Py substituted ligands 2 and 3 differs from that in the above described complexes. The measured specific magnetic susceptibility χ r of cobalt complex 3a is 13.36•10 -6 cm 3 g -1 at 293.8 K. The effective magnetic moment of complex 3a calculated from this value is 5.09 µ B , which agrees well with the published data 26 for the octahedral Co II complexes (4.7-5.2 µ B ).…”
Section: Resultsmentioning
confidence: 67%
“…Copper containing complexes were able to inhibit number of polymerases that allowed us to hypothesize that interaction of copper containing complexes with the proteins in the vicinity of DNA may result in copper ions release that cause DNA damage followed by rapid DNA degradation by cellular nucleases. Experiments with mice models showed that complex 2 is less toxic than well-known drug cisplatin 28 and have pronounced antitumor effect. Novel class of metal complexes,based on 2-thioxoimidazol-2-one heterocyclic core could be utilized as a smart platform for construction of anticancer chemotherapy agents.…”
Section: Discussionmentioning
confidence: 99%
“…Materials. Initial 2-thioxo-5-(pyridine-2-ylmethylene)-3,5-dihydro-4H-imidazole-4-ones were prepared previously by Beloglazkina 28 . General method for the synthesis of L1-L6.Selected 2-thioxo-5-(pyridine-2-ylmethylene)-3,5-dihydro-4H-imidazole-4-on (2 equivalents), α,ω-dibromoalkane (1 equivalent) and solid potassium carbonate (3 equivalents) were suspended in DMF (10 ml) at 0 0 С.…”
Section: Methodsmentioning
confidence: 99%
“…5,5-Diphenyl-2-thiohydantoin (2-thiophenytoin) is a well-known derivative of 2-thiohydantoin that has attracted the attention of medicinal chemists (14).…”
Section: Introductionmentioning
confidence: 99%